2016
DOI: 10.1016/j.phrp.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Inequality in the Incidence and Mortality of Nasopharynx Cancer in Asia

Abstract: ObjectivesOne of the most common head and neck cancers is nasopharynx cancer. Knowledge about the incidence and mortality of this disease and its distribution in terms of geographical areas is necessary for further study and better planning. Therefore, this study was conducted with the aim of determining the incidence and mortality rates of nasopharynx cancer and its relationship with the Human Development Index (HDI) in Asia in 2012.MethodsThe aim of this ecologic study was to assess the correlation between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 36 publications
(44 reference statements)
3
76
0
Order By: Relevance
“…Head and neck squamous cell carcinoma poses a significant public health burden in the Asia‐Pacific region. The global incidence of HNSCC tops 600 000 cases annually, with more than half of all cases originating in the Asia‐Pacific region . In addition to the traditional HNSCC risk factors (ie, tobacco and alcohol use and human papillomavirus infection), other cultural influences, such as the chewing of betel nut, the consumption of products high in nitroso compounds, and exposure to Epstein–Barr virus, contribute to an increase in the occurrence of HNSCC in this region …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck squamous cell carcinoma poses a significant public health burden in the Asia‐Pacific region. The global incidence of HNSCC tops 600 000 cases annually, with more than half of all cases originating in the Asia‐Pacific region . In addition to the traditional HNSCC risk factors (ie, tobacco and alcohol use and human papillomavirus infection), other cultural influences, such as the chewing of betel nut, the consumption of products high in nitroso compounds, and exposure to Epstein–Barr virus, contribute to an increase in the occurrence of HNSCC in this region …”
Section: Introductionmentioning
confidence: 99%
“…HNSCC tops 600 000 cases annually, with more than half of all cases originating in the Asia-Pacific region. [1][2][3] In addition to the traditional HNSCC risk factors (ie, tobacco and alcohol use and human papillomavirus infection), 4,5 other cultural influences, such as the chewing of betel nut, the consumption of products high in nitroso compounds, and exposure to Epstein-Barr virus, contribute to an increase in the occurrence of HNSCC in this region. [6][7][8] In Asia, a multimodal approach that combines platinum-based chemotherapy, radiotherapy, and another agent (preferably cetuximab), is recommended for the treatment of patients with recurrent/ metastatic HNSCC.…”
mentioning
confidence: 99%
“…More and more attentions were paid on the nasopharyngeal carcinoma (NPC) for its high incidence rates in Asia. Data from IARC showed that the incidence rates of NPC were up to 71.02% for men, which was nearly 2.45 times higher than that of women in Asian countries, especially in the country of Malaysia, Singapore, Indonesia and China (Mahdavifar et al, 2016). Currently, the traditional surgery combined with chemoradiotherapy was widely applied during its therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma is an EBV‐associated epithelial carcinoma, and is common in South China and Southeast Asia (Figure ) . More than 97% of NPC are EBV‐positive, and the tight link between NPC and EBV is observed worldwide .…”
Section: Ebv Strain Variation: Geographic or Disease‐specific?mentioning
confidence: 99%
“…Nasopharyngeal carcinoma is an EBV-associated epithelial carcinoma, and is common in South China and Southeast Asia (Figure 1). 12 More than 97% of NPC are EBV-positive, 13 and the tight link between NPC and EBV is observed worldwide. 3 Several predisposing factors have been postulated, including host immune-related genes such as human leukocyte antigens, 14 and environmental factors such as dietary habits (i.e.…”
mentioning
confidence: 99%